Integrasi Kearifan Lokal Madurologi Pada Pembelajaran Ilmu Pengetahuan Sosial : Upaya Melestarikan Falsafah Leluhur Masyarakat Madura - Tri Sutrisno (IAIN Madura, 2025)
This research aims to identify and analyze the values of Madurese local wisdom (Madurology) in SDN Kalianget Barat III that can be integrated in Social Studies learning in elementary schools, as well as its relevance to the current educational context. Furthermore, this research will develop an applicable integration model, where Madurese cultural values can be applied in social studies learning materials to help teachers introduce and teach local culture to students effectively. The research method used in this study is a qualitative approach. This approach was chosen because the purpose of the research was to explore deeply about how the integration of Madurese local wisdom (Madurology) in Social Studies learning in elementary schools. This research was conducted at SDN Kalianget Barat III Sumenep, which is located in the Madura region. This school was chosen because it is considered to have potential in developing Madurese local wisdom-based learning, and has characteristics that can represent the implementation of local culture in learning in elementary schools. The results showed that historically, Madura has an important role in the formation of national identity through cultural, social and political contributions. Madurese people uphold the principle of andhap asor (humble), kinship ethics (bung-sabung rosok), work toughness (ta'tako' mate, tape tako'kalaparan), and morality (Bhupa' Bhebu' Guru Rato). These values not only enrich social studies material on cultural diversity, social norms, and citizenship, but also shape the character of students who are noble, respect brotherhood, and have a high work ethic. The integration of local wisdom in social studies learning can be done through contextual approaches such as collaborative projects, role-playing, and case discussions, which are adjusted to the grade level and geographical conditions in Madura.